Postural Motor Learning Deficits in People With MS in Spatial but Not Temporal Control of Center of Mass. (September 2016) - Gera, Geetanjali; Fling, Brett W.; Van Ooteghem, Karen; Cameron, Michelle; Frank, James S.; Horak, Fay B.
Background: Multiple sclerosis (MS) is associated with balance deficits resulting in falls and impaired mobility. Although rehabilitation has been recommended to address these balance deficits, the extent to which people with MS can learn and retain improvements in postural responses is unknown.Aim: To determine the ability of people with MS to improve postural control with surface perturbation training.Methods: A total of 24 patients with mild MS and 14 age-matched controls underwent postural control training with a set pattern of continuous, forward-backward, sinusoidal, and surface translations provided by a force platform. Postural control was then tested the following day for retention. The primary outcome measures were the relative phase and center-of-mass (CoM) gain between the body CoM and the platform motion.Results: People with MS demonstrated similar improvements in acquiring and retaining changes in the temporal control of the CoM despite significant deficits in postural motor performance at the baseline. Both MS and control groups learned to anticipate the pattern of forward-backward perturbations, so body CoM shifted from a phase-lag (age-matched controls [CS] = −7.1 ± 1.3; MS = −12.9 ± 1.0) toward a phase-lead (CS = −0.7 ± 1.8; MS = −6.1 ± 1.4) relationship with the surface oscillations. However, MS patients were not able to retain the changes in the spatial control of the CoM acquired during training.Conclusions: People with MS have the capacity to improve use of a feed-forward postural strategy with practice and retain the learned behavior for temporal not spatial control of CoM, despite their significant postural response impairments.